Matrix Gla protein jako přirozený inhibitor vaskulárních kalcifikací a potenciální léčebný cíl - Mayer, Otto (Casopis lekaru ceskych, 2016)
Vascular calcification was once regarded as an advanced stage of atherosclerosis only. However, calcification is currently considered as highly regulated and potentially reversible process.Matrix Gla protein (MGP) represents natural inhibitor of vascular calcification, whereas vitamin K is key co-factor of its maturation to the active form. There is accumulating evidence that vitamin K status and corresponding MGP activity may influence cardiovascular risk. This review summarizes pathophysiological mechanism and recent evidence relative to MGP. Moreover, available data concerning vitamin K supplementation are depicted.
Keywords: matrixový protein Gla; Antifibrinolytic Agents; Humans; extracelulární matrix - proteiny; vitamin K; matrix Gla protein; Calcium-Binding Proteins; vaskulární kalcifikace; rizikové faktory; antifibrinolytika; lidé; cardiovascular diseases.; Extracellular Matrix Proteins; Matrix Gla Protein; Vascular Calcification; proteiny vázající vápník; potravní doplňky; Dietary Supplements; Vitamin K; vascular calcifications; Risk Factors